Glutathione - Flohe, Leopold; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This is the first serious attempt to synthesize all that became known of glutathione over the last three decades. The book contains an update of glutathione biosynthesis with special emphasis on its regulation in adaptive stress responses. Other chapters review glutathione transport systems and glutathione peroxidases and their differences in substrate specificities and localization. Further contributions center on the diversified roles of different glutathione-S-transferases and the roles of nitrosoglutathione and glutaredoxins - a subfamily of redoxins. The book closes with discussions of the analogous or homologous thiol metabolism in pathogens and the potential suitability of involved enzymes as drug targets.
Contents -- Series Preface.......................................................xi -- Editors Preface.................................................... xiii -- Editor Biography...................................................xix -- List of Contributors .................................................xxi -- --Part I Biosynthesis, Compartmentation, -- and Transport of Glutathione -- Chapter 1 --Biosynthesis of Glutathione and Its Regulation..................3 -- --Henry J. Forman, Hongqiao Zhang, and Terrance J. Kavanagh -- Chapter 2 --Renal Glutathione Transport Systems: Roles in Redox -- Homeostasis, Cytoprotection, and Bioactivation................ 35 -- --Lawrence H. Lash -- Part II Glutathione-Dependent -- Hydroperoxide Metabolism -- Chapter 3 --The Catalytic Mechanism of Glutathione Peroxidases............ 53 -- --Laura Orian, Giorgio Cozza, Matilde Maiorino, Stefano -- Toppo, and Fulvio Ursini -- Chapter 4 --GPx1-Dependent Regulatory Processes in Health and Disease..... 67 -- --Diane E. Handy and Joseph Loscalzo -- Chapter 5 --Glutathione Peroxidase 1 as a Modulator of Insulin Production -- and Signaling: Implications for Its Dual Role in Diabetes......... 81 -- --Holger Steinbrenner and Lars-Oliver Klotz -- Chapter 6 --GPx2 Role in Physiology and Carcinogenesis..................95 -- --Anna P. Kipp -- Chapter 7 --GPx4: From Prevention of Lipid Peroxidation to -- Spermatogenesis and Back................................ 111 -- --Matilde Maiorino, Antonella Roveri, and Fulvio Ursini -- Chapter 8 --Thiols, Glutathione, GPx4, and Lipid Metabolism at the -- Crossroads of Cell Death and Survival....................... 129 -- --Jos Pedro Friedmann Angeli, Valerian E. Kagan, and Marcus -- Conrad -- Chapter 9 --Peroxiredoxin 6 as Glutathione Peroxidase................... 143 -- --Yefim Manevich -- Chapter 10 --Glutathione Peroxidases and the Thyroid Gland............... 161 -- --Lutz Schomburg -- Part III Conjugations and Isomerizations -- Chapter 11 --Glutathione Transferases: From the Test Tube to the Cell........ 175 -- --Bengt Mannervik and Birgitta Sjdin -- Chapter 12 --Protein S-Glutathionylation and Glutathione S-Transferase P..... 201 -- --Kenneth D. Tew -- Chapter 13 --The Role of Glutathione in Biosynthetic Pathways and -- Regulation of the Eicosanoid Metabolism.................... 215 -- --Ralf Morgenstern, Leopold Floh, Jesper Z. Haeggstrm, and -- Per-Johan Jakobsson -- Chapter 14 --Nitric Oxide and S-Nitrosoglutathione.......................227 -- --Iain L. O. Buxton and Scott D. Barnett -- Part IV The Glutaredoxins -- Chapter 15 --The Catalytic Mechanism of Glutaredoxins................... 251 -- --Linda Liedgens and Marcel Deponte -- Chapter 16 --The Role of Glutaredoxins in the Brain......................263 -- --Carsten Berndt, Anna Dorothee Engelke, Klaudia Lepka, and -- Lars Brutigam -- Part V Glutathione Derivatives and -- Substitutes in Pathogenic Microorganisms -- Chapter 17 --Biosynthesis of PolyamineGlutathione Derivatives in -- --Enterobacteria and Kinetoplastida..........................285 -- --Marcelo A. Comini -- Chapter 18 --Trypanothione Functions in Kinetoplastida...................307 -- --Martn Hugo, Madia Trujillo, Luca Piacenza, and Rafael Radi -- Chapter 19 --Mycothiol, a Low-Molecular-Weight Thiol Drafted for -- Oxidative Stress Defense Duty............................. 331 -- --Leonardo Astolfi Rosado, Brandn Pedre, and Joris Messens -- Chapter 20 --Biosynthesis and Functions of Bacillithiol in Firmicutes......... 357 -- --Quach Ngoc Tung, Nico Linzner, Vu Van Loi, -- and Haike Antelmann -- Index--............................................................ 379.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Life Sciences / Cytology; SCIENCE / Life Sciences / Biology / Molecular Biology; Adaptive Stress Response; Biosynthesis; Detoxification; Drug Discovery; Redox Reactions; Glutathione -- Congresses; Glutathione -- Metabolism -- Congresses; Glutathione; Glutathione -- Metabolism; Electronic books